A comparative assessment of functioning of Basic and Specialised Medical Emergency Teams belonging to the Independent Public Complex of Healthcare Centres in Staszów - Musiał, Paweł (Journal of Education, Health and Sport, 2019)
Creating a medical emergency system is a long-lasting and demanding process. It requires experience and the cooperation of a range of environments: medical, administrative, and political ones. In the development of system solutions in medical rescue and emergency medicine in Europe the main role is played by two systemic patterns: French-German (FSG) and Anglo-American (AAS) ones. The names of the aforementioned systems originate from the countries in which these ideas were born and shaped. Currently, most medical emergency systems in the world are a combination of solutions derived from these particular models. A common feature of both systems is to provide emergency assistance in accidents and injuries, as well as in sudden cases of falling ill. The differences relate mainly to the degree of using basic and advanced life-saving procedures at the scene of an accident.